A Comprehensive Study of the Different Parameters of Solar Still - Lal R.K.; Mishra S.; Dwivedi J.P.; Dwivedi H. (My University, 2025)
Many literature and experimental papers on different aspect of solar still has been studied. Literature review shows that approximately 99% of available water on Earth is salty, brackish and frozen and that only 1% is fresh and used as hygienic water.One of the parameters that have received a considerable attention is the glass tilt angle. Enough number of studies on the effect of cover tilt angle on productivity in different seasons and latitude are included in this article, this article also include depth of brine, direction of solar still and mathematical equation for wick type still which applies generally. In this paper, the different effect of parameter on active and passive type solar still is including.This review also including the important equations and their significance. © 2017 Elsevier Ltd. All rights reserved.